Microalgae as a Feedstock for Biofuels - Gouveia, Luisa; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This Brief provides a concise review of the potential use of microalgae for biofuel production. The following topics are highlighted: the advantages of microalgae over conventional biofuel-producing crops; technological processes for energy production using microalgae; microalgal biomass production systems, production rates and costs; algae cultivation strategies and main culture parameters; biomass harvesting technologies and cell disruption; CO2 sequestration; life cycle analysis; and algal biorefinery strategies. The conclusions section discusses the contribution of the technologies described to environmental sustainability and future prospects.
Introduction -- Microalgae and biofules production -- Microalgal biomass production -- algal cultivation -- CO2 sequestration -- Microalgal biomass harvesting -- Cell disruption -- Production rates, production and processing costs -- Life cycle analysis -- Modelling approaches -- Algal biorefinery strategy -- Conclusions.
Keywords: Life sciences; Renewable energy resources; Cell culture; Microbiology; Renewable energy sources; Alternate energy sources; Green energy industries; Environmental engineering; Biotechnology; Life Sciences; Microbiology; Renewable and Green Energy; Environmental Engineering/Biotechnology.; Cell Culture; Renewable and Green Energy; Electronic books